Past and present geographical distribution of populations of Portuguese (Crassostrea angulata) and Pacific (C. gigas) oysters along the European and north African Atlantic coats - Fabioux, Caroline; Huvet, Arnaud; Lapegue, Sylvie; Heurtebise, Serge; Boudry, Pierre (Société Française de Malacololgie, 2002)
Today, it is commonly accepted that C. angulata and C. gigas are a single species according to morphological, genetic and experimental hybridization data. Following the viral disease that affected C. angulata and the subsequent expansion of C. gigas in Europe, it was of interest to examine the geographical distribution of both taxa in Europe. We studied the genetic composition of seventeen populations of cupped oysters, sampled in France, Spain, Portugal, Morocco and Italy, using a diagnostic marker, the mitochondrial Cytochrome Oxydase I gene. Results showed two distinct geographical zones. All the populations located in the northern part of the European sampled zone were mainly composed of C. gigas haplotypes whereas populations from southern Europe and Morocco were mainly composed of C. angulata haplotypes. No natural populations were found between Coruña (northern Spain) and Lisbon (western Portugal). Very limited mixtures of the two taxa were observed in France and northern Spain, which might correspond to ancestral polymorphism and suggest the past presence of C. angulata in these regions. However, some notable mixtures were observed in the south of Portugal. This could be the result of importation of C. gigas spat to this region. These results indicate a recent change in genetic composition of populations in southern Portugal and show that human activities have created contact zones between the two taxa although no natural sympatric zones exist in Europe. Les deux huîtres creuses Crassostrea gigas et Crassostrea angulata sont aujourd'hui communément classées dans la même espèce du fait de leur similarité morphologique et génétique et de leur hybridation en conditions expérimentales. La forte expansion de C. gigas en Europe ayant succédée à la disparition des populations de C. angulata, affectées par une infection virale, il était intéressant d'étudier la distribution actuelle des deux taxons d'huîtres en Europe. Dans la présente étude, la composition génétique de dix-sept populations d'huîtres creuses ...